Inovasi Sosial Dalam Pemberdayaan Masyarakat Agrowisata: Studi Kasus Kampung Flory, Sleman - Mushonnif, Mushonnif; Fajar, Adam Hafidz Al; Mudfainna, Mudfainna; Syamraeni, Syamraeni (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
Social innovation has become a key approach in empowering communities based on local potential, particularly in the development of agriculture-based tourism or agrotourism. Flory Village in Sleman serves as a concrete example of transforming a conventional agricultural area into a community-based, inclusive, and sustainable agrotourism destination. This study aims to explore the practice of social innovation in community empowerment in Flory Village, focusing on the types of innovation implemented, the actors involved, and the strategies used to drive social change. This research employs a qualitative approach through field study. Data were collected using in-depth interviews with five main informants—members of the tourism awareness group (Pokdarwis), village officials, and tourism office representatives—participatory observation during various village activities, and document analysis, including institutional reports, promotional materials, and local media. Data validity was ensured using source triangulation. The results show that the success of Flory Village lies in strong cross-sector collaboration, digital technology integration, and continuous capacity building. Social innovation not only contributes to economic development but also strengthens social cohesion and community identity.